The Influence of Social Media and Peer Interaction on Students’ English Writing Proficiency - Siti Masluha; Rasyidah Nur Aisyah; Regita Febriyanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study looks at how students in the English Department at Universitas Panca Marga's writing skills change when they use social media and have organized interactions with their peers. Participants were chosen using a saturated sampling method, and the study used a quantitative method analyzed through SmartPLS software. The level of English writing skills was the dependent variable, and the amount of time spent on social media and structured peer contact were the independent variables. Multiple signs were used to measure each variable, and reliability and validity tests were used to evaluate them. The results indicate that both using social media and structured peer interaction have a good impact on students' writing skills, with structured peer interaction having a bigger effect. Participating in social media helps build vocabulary and writing speed, and working with others in an organized way improves grammar, coherence, and the ability to think critically about what you've written. These results show that digital and collaborative learning settings work hand-in-hand to help students improve their writing. The study suggests that students can improve their writing skills by doing structured peer activities and seeing real English material on social media. It gives useful advice to teachers who want to improve the way they teach writing and ideas for more study into how digital and interactive learning strategies work together in language classes.